PELATIHAN CANVA BAGI PENGGAGAS UKM DESA JIWO WETAN DALAM RANGKA PENINGKATAN BRANDING UMKM KLATEN - Lutfiyani, Rizka Safitri; Joko Prasetiyo, Hendro; Sulistyowati, Istri; Windarti, Mariana (LPPM Universitas Widya Dharma Klaten, 2024)
MSME (Micro Small Medium Enterprise) have biggest impact for Indonesian Economy. 99 percent of industry in Indonesia is MSME. However, they still have to struggle for the marketing aspect. That can be happen because they underestimate the power of branding. Jiwo Wetan is one of village in Klaten Regency. MSME in Jiwo Wetan have same problem too. They have never been create poster or logo their product. So, this community service activities would to explained about branding. Moreover, the team of community service activities University of Widya Dharma Klaten would to organize a branding training with Canva Application to them. This activities is expected to introduce branding to them and give them slightly ability to use Canva Application.